Unlocking the Potential: Probiotics as a Promising Frontier in Oral Health - Narahari Ranganatha; TV Pracheth; Shwetha Narayani; Shobhit K Saxena; Anand N. Wankhede; Nivedita Sahoo; Pratik Surana (Wolters Kluwer Medknow Publications, 2024)
Probiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit on the host. The role of probiotics in promoting oral health has gained attention in recent times Current literature aims to provide an outline of the application of probiotics in dentistry, focusing on their various formulations and potential benefits in oral health. The rationale for using probiotics in dental care, their different applications, and the future prospects of probiotics in dentistry will be discussed.